1999
DOI: 10.1063/1.371609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quantum well location on single quantum well p-i-n photodiode dark currents

Abstract: The photocurrent available from a p-i-n solar cell can be increased by the addition of quantum wells ͑QWs͒ to the undoped region. At the same time the QWs reduce the open-circuit voltage by introducing areas of lower band gap where recombination is enhanced. This increase in recombination should be as small as possible for the most favorable effect on the photovoltaic efficiency of the device. Theoretical considerations indicate that nonradiative recombination, which is the dominant loss mechanism in Al x Ga 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 20 publications
0
30
0
1
Order By: Relevance
“…This increase in efficiency is consistent with earlier experimental results. 21 We observe that QD should not be in direct contact with the edge of either the p or n region, in order to avoid the accumulation of the majority carriers that deteriorate the carrier transport at the shortcircuit condition. The variation of efficiency η with position x of the QD are similar for n i = 10 10 and N B = 10 13 .…”
mentioning
confidence: 86%
“…This increase in efficiency is consistent with earlier experimental results. 21 We observe that QD should not be in direct contact with the edge of either the p or n region, in order to avoid the accumulation of the majority carriers that deteriorate the carrier transport at the shortcircuit condition. The variation of efficiency η with position x of the QD are similar for n i = 10 10 and N B = 10 13 .…”
mentioning
confidence: 86%
“…69 The reduction of the V oc was mainly attributed to SRH recombination, which showed the maximum value when the electron and hole density were similar at the place such as the center of the intrinsic region. 66 They have also fabricated three samples experimentally with the three QD locations mentioned above to verify the simulated results. 69 Figure 8(a) summarized the EQE results for the three samples along with the baseline GaAs cell.…”
Section: Effect Of Quantum Dot Location On Carrier Transportation Andmentioning
confidence: 99%
“…41,[66][67][68] Driscoll et al 69 performed simulations on three positions for InAs QD located in the intrinsic region: (1) near the n-doped base, (2) exact center of i-region, and (3) near the p-doped emitter. 69 From the simulation, they found that J sc was nearly identical for the three positions as all were located in a high electric field region and carrier collection remained efficient for all three conditions.…”
Section: Effect Of Quantum Dot Location On Carrier Transportation Andmentioning
confidence: 99%
“…Nelson et al found that the background doping of the intrinsic region played a key role on the process and that a careful placement of the QWs away from the region where minority carrier densities were similar helped to reduced non-radiative recombination 24 .…”
Section: Addressing the Non-radiative Lossesmentioning
confidence: 99%